Pengaruh Realisasi Anggaran Pendapatan Dan Belanja Daerah (APBD) Terhadap Pertumbuhan Ekonomi Kota Medan - Lubis, Putri Kemala Dewi; Simbolon, Nur Aini; Sinaga, Sasmi Ebigiel; Gultom, Grace Amelia Margareth; Siagian, Arnol Prabowo (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the effect of the realization of the Regional Revenue and Expenditure Budget (APBD) on economic growth in Medan City, as well as to identify factors that influence the effectiveness of APBD realization and the challenges faced by the Medan City Government in realizing the budget. The research method used is a quantitative approach, which aims to test the causal relationship between the independent variable (APBD realization) and the dependent variable (economic growth). The data used in this study are secondary data in the form of figures or statistical data obtained from the annual reports of the Medan City Government and the Medan City Central Statistics Agency (BPS) for the period 2001-2023. This data includes information on the realization of the regional revenue and expenditure budget and the PDRB of Medan City as an indicator of economic growth. To analyze the data, the multiple linear regression method was used through the Eviews application, which allows testing the simultaneous influence between APBD realization and economic growth. The results of this study are expected to provide a deeper understanding of how APBD management affects economic growth in Medan City, as well as the factors that influence the effectiveness of regionalbudgetimplementation.